DINAMIKA KEBIJAKAN TENTANG PERIKANAN DAN TRANSFORMASI BUDAYA NELAYAN PANTAI UTARA JAWA - Widodo, Sutejo K. (Fakultas Ilmu Budaya Universitas Diponegoro, 2011)
Rice and fish could be complementing each other as human primary needs for nutrition. However, both these commodities have a history with the opposite. Although Java island is surrounded by the waters of the sea, in the past the population in meeting the needs of fish, mainly marine fish, mostly done by the fishermen who brought in fish catches from other areas or imported, in the form of salted fish and dried fish, since the Dutch colonial government and gradually began to set the political self-sufficient self-reliance in the 1960s. This article discusses the dynamics of policy on fishing in the north coast of Java, with a historical approach with a span of years 1900 to 2000.